Course enhancement conversations: A holistic and collaborative evaluation approach to quality improvement in higher education. (December 2022) - Forbes, Melissa; Murphy, Angela; Alderman, Lyn
This practice article describes the use of collaborative evaluation for institutional improvement leading to continuous learning at a regional university in Australia. The University of Southern Queensland's Academic Quality Framework (2019–2022) was developed in response to external drivers to improve practices relating to the comprehensive and systematic analysis of academic data. One aspect of the response was to introduce 'course enhancement conversations', which were a collaboration between the central Academic Quality Unit and academic staff, including course teams and learning and teaching leaders within schools and faculties. A feature of these conversations was the use of sentinel rather than performance indicators of course (not teaching) quality to prompt the holding of conversations. Conversations were conducted in a spirit of constructive collaboration, where the shared goal was to support course teams to deliver an outstanding student experience. Through adopting a collaborative approach to evaluation, Academic Quality Unit staff were evaluation champions who gradually acculturated academic staff and learning and teaching leaders to evaluative thinking and data-informed decision-making. Issues brought to light during these conversations have informed changes in practice at the university level, including the development of a new evaluation procedure to embed best-practice monitoring and evaluation across all levels of curriculum delivery.